Pre- and post-adolescents' physiological response to exercise. Issue 4 (December 1981) - Bale, P.
Abstract : The physiological performance of a group of boys and girls aged eleven to twelve years was examined and nineteen of these children were retested again at aged sixteen years. The findings of this investigation support the findings of other similar studies that, when VO2 max is used as a determinant of cardiovascular performance, the performance of children increases with age, and in boys particularly, this increase in associated with an increase in body weight. After puberty boys have a greater oxygen consumption and thus a greater physiological performance than girls, mainly as a result of an improved cardiorespiratory efficiency and a greater muscle to weight ratio. The improvement in their physiological performance by those girls particularly interested in sport, however, also suggests that this factor is most influential to performance during growth at adolescence.